(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to study the role of human capital in its dimensions in developer strategic performance by applying to public manufacturing companies in Syria. To achieve this, a main hypothesis was formulated, from which five sub hypotheses are branched, and the researcher used a questionnaire method to collect data. The researcher has reached several results, the most important of which are: The public companies for the manufacturing industries under study possess human resources that constitute good human capital in terms of the availability of dimensions related to knowledge, skills, abilities, experience, innovation, cooperation and work spirit, which is the minimum required that must be met at least in any An industrial company, but it does not rise to the distinguished level that makes human resources a real capital, as these companies suffer from not investing these resources effectively as a result of many circumstances and other factors that limit their ability to do so, which will negatively affect their ability to achieve performance. Strategic, where there is a weak direct relationship between the human capital available in the companies under study and their ability to achieve strategic performance.